Data informed leadership: the work of primary mathematics lead teachers in New Zealand. Issue 1 (1st January 2021) - Edwards, Frances; Ogle, Dianne
ABSTRACT: Increasingly, teachers are considered accountable for continuous improvement in student achievement. They are expected to integrate and analyse data from multiple sources in order to make decisions aimed at positively influencing student outcomes. Given the growing recognition of the importance of data-informed decision making in teaching, it is important to understand how teachers can best be supported in this. Currently, there is little research into how teachers can facilitate data literacy development for their in-school colleagues. This study employed an interpretive qualitative methodology to focus on the experiences of mathematics lead teachers (MLTs) in leading change to support the development of their colleagues. MLTs were found to use a range of tailored strategies, providing 'on the job' and 'just in time' support, and demonstrating evaluative and adaptive capabilities. They were found to provide leadership in the development of data-informed decision making through their collaborative approach.